The Effect of Job Training, Intrinsic Motivation, Individual Characteristics on Work Productivity of DI Yogyakarta Tourism Office Employees - Arryanto Arryanto; Syamsul Hadi; Epsilandri Septyarini (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine the effect of job training, intrinsic motivation, individual characteristics on the work productivity of the Yogyakarta Special Region Tourism Office employees. This study used a sample of the entire population who had attended job training as many as 65 employees at the Yogyakarta Special Region Tourism Office. Sampling in this study using saturated sampling technique. The data collection method uses a questionnaire using a Likert scale size of 1-5. Furthermore, the validity test and reliability test were carried out. The data analysis technique used is multiple linear regression. The results showed that partially and simultaneously variable X had a positive and significant effect on variable Y.